Turning the world upside down a century of missionary endeavour - Echoes of Service; Stunt, William Thornburgh, 1909-; Pulleng, Alexander, 1897-; Pickering, Arnold, 1908-; Simmons, George Philip, 1901-; Boak, Donald Kenneth, 1930-; Warren, Stanley Francis, 1919- (Eastbourne, UK Upperton, 1973)
Includes indexes.
Keywords: Brethren movement -- missions -- history